Study on preparation and some thermal-mechanical characteristics of composite material based on phenolic/fiberglass - Đoàn Văn Phúc; Trần Xuân Tiến; Nguyễn Tiến Mạnh; Đỗ Quốc Mạnh (Journal of Military Science and Technology, 2022)
The article presents some results on preparing and determining the mechanical and thermal resistance of composite materials based on phenolic resin/fiberglass, oriented using for the heat-protective layer of the bottom of rocket engine B72. The research results show that the composites based on a modified phenolic resin and heat-resistant fiberglass T11 have higher specific heat and thermal and mechanical strength in comparison with the AG-4V material ГОСТ 20437-89. The test results of the heat-shielding ability through an oxygen-acetylene flame at 2100 °C showed that this material could be used as a heat-shielding layer for the bottom of rocket engine B72.